Chronic abdominal aortic dissection, endovascular treatment using a new Stent-graft for in situ Fenestration - Hernan G. Bertoni; German A. Girela; Hector D. Barone; Federico De Caso; Alejandro De La Vega; Bao T. Bui; Thomas Maldonado (CVIR Endovascular, 2021)
Abstract Background Although endovascular treatment of the thoracic aorta (TEVAR) has become an elective procedure for treatment of complicated type B aortic dissection, its role in treating post dissection thoraco-abdominal aortic aneurysm (TAAA), is still limited. This is a case of aortic vascular disease, which reports the use of a new endovascular device. Case presentation : We present the case of a 62 year old male patient with a history of hypertension, active smoker, who presented penetrating descending thoracic aortic ulcer in the setting of a chronic abdominal aortic dissection. The patient was treated using a new stent graft capable of in situ fenestration that allowed crossing the stent-graft membrane, implanting a covered stent to exclude the re-entry at the level of the left renal artery and redirecting the blood flow through the true lumen. Conclusions This case report demonstrates the feasibility of a novel stent-graft concept. Larger studies with longer follow-up are essential to fully evaluate the safety and effectiveness of this new design.